Epididymal protease inhibitor (EPPIN) is a protein hub for seminal vesicle-secreted protein SVS2 binding in mouse spermatozoa - Mariani, Noemia A.P. [UNESP]; Camara, Aline C. [UNESP]; Silva, Alan Andrew S. [UNESP]; Raimundo, Tamiris R.F. [UNESP]; Andrade, Juliana J. [UNESP]; Andrade, Alexandre D. [UNESP]; Rossini, Bruno C. [UNESP]; Marino, Celso L. [UNESP]; Kushima, Hélio [UNESP]; Santos, Lucilene D. [UNESP]; Silva, Erick J.R. [UNESP] (Elsevier, 2020)
EPPIN is a sperm-surface drug target for male contraception. Here we investigated EPPIN-interacting proteins in mouse spermatozoa. We showed that EPPIN is an androgen-dependent gene, expressed in the testis and epididymis, but also present in the vas deferens, seminal vesicle and adrenal gland. Mature spermatozoa presented EPPIN staining on the head and flagellum. Immunoprecipitation of EPPIN from spermatozoa pre-incubated with seminal vesicle fluid (SVF) followed by LC-MS/MS or Western blot revealed the co-immunoprecipitation of SVS2, SVS3A, SVS5 and SVS6. In silico and Far-Western blot approaches demonstrated that EPPIN binds SVS2 in a protein network with other SVS proteins. Immunofluorescence using spermatozoa pre-incubated with SVF or recombinant SVS2 demonstrated the co-localization of EPPIN and SVS2 both on sperm head and flagellum. Our data show that EPPIN's roles in sperm function are conserved between mouse and human, demonstrating that the mouse is a suitable experimental model for translational studies on EPPIN.
Keywords: EPPIN; Male contraception; Mouse; Spermatozoa; SVS2